Typology assessment of dairy cattle production in the major productive region of Tunisia. - hamzaoui, SARRA (Indian Journal of Dairy Science, 2026)
The study aimed to identify dairy systems related to purebred cattle in Tunisia and their effects on milk production and quality. A survey of 102 breeders across 17 governorates focused on feeding practices and milk parameters. Principal Component Analysis (PCA) revealed three farm groups: Group I (51% of farms) relies on rainfed systems with limited forage; Group II (26%) employs mixed irrigation with moderate forage; and Group III (23%) uses irrigation, featuring larger farms and diverse diets. Significant differences were observed among groups in terms of farm size, cow numbers, and diet composition (P